COPD Causation and Workplace Exposures: An Assessment of Agreement among Expert Clinical Raters. (21st March 2013) - Fishwick, David; Darby, Anthony; Hnizdo, Eva; Barber, Chris; Sumner, Jade; Barraclough, Richard; Bolton, Charlotte; Burge, Sherwood; Calverley, Peter; Hopkinson, Nick; Hoyle, Jennifer; Lawson, Rod; et al.
Abstract Background. Although occupational exposure is a known risk factor for Chronic Obstructive Pulmonary Disease (COPD), it is difficult to identify specific occupational contributors to COPD at the individual level to guide COPD prevention or for compensation. The aim of this study was to gain an understanding of how different expert clinicians attribute likely causation in COPD. Methods. Ten COPD experts and nine occupational lung disease experts assigned occupational contribution ratings to fifteen hypothetical cases of COPD with varying combinations of occupational and smoking exposures. Participants rated the cause of COPD as the percentage contribution to the overall attribution of disease for smoking, occupational exposures and other causes. Results. Increasing pack-years of tobacco smoking was associated with significantly decreased proportional occupational causation ratings. Increasing weighted occupational exposure was associated with increased occupational causation ratings by 0.28% per unit change. Expert background also contributed significantly to the proportion of occupational causation rated, with COPD experts rating on average a 9.4% greater proportion of occupational causation per case. Conclusion. Our findings support the notion that respiratory physicians are able to assign attribution to different sources of causation in COPD, taking into account both smoking and occupational histories. The recommendations on whether to continue to work in the same job also differ, the COPD experts being more likely to recommend change of work rather than change of work practice.